A new cave species of the genus Gymnaetoides (Rhaphidophoridae: Aemodogryllinae: Aemodogryllini) from Guizhou, China - Feng, Xueli; Huang, Shihui; Luo, Changqing (Zootaxa, 2020)
In this study, a new species of the genus Gymnaetoides Qin, Liu & Li, 2017, namely Gymnaetoides polaoensis sp. nov., from a karst cave in Guizhou Province, China is described. This new species is the first cave-dwelling species belonging to the genus Gymnaetoides. The morphological photographs of the males of this new cave species are provided.